A collaborative image of energy efficient housing via a photo-based approach. Issue 3 (4th November 2019) - Poor, Javad Asad; Thorpe, David; Goh, Yong Wah
Abstract : Purpose: Regarding the contribution of Australian small-size housing in the enhancement of total energy consumption of the country and the roles of the occupants' preferences in successful implementation of action plans, the purpose of this study is to identify the Australian occupants' collaborative image of housing energy efficiency. The two main objectives are, therefore, to address the main energy-related housing physical factors that have the potential in representing the housing image of Australian occupants and to explain the causal factors that make the physical factors critical to their energy efficiency perception. Design/methodology/approach: This study has been developed through a qualitative approach. Given that the images encompass a wide range of information expressing human perceptions, an online photo-based qualitative survey was developed based on previous research works. The survey includes respondents' demographic profiles and the evaluation of images, asking for their perception of overall housing energy efficiency, the impacts of building envelope physical attributes on the energy efficiency of the houses and the reasons behind the selection of different attributes. Findings: This study has developed a set of attribute-based factors, explaining occupants' collective perception of energy efficient small-size housing of Brisbane in the area of exterior aspects of the buildings. Specifically, the collaborative image of small-size housing of Brisbane is about the thermal performance of the buildings provided through passive climatic principles by using more efficient envelope features, e.g. material, colour, transparency, texture, openings, balconies and shadowing devices, while ignoring the impacts of architectural composition principles along neighbourhood quality. The key attributes in assessing the small-housing energy efficiency are ventilation, thermal performance and shadowing. The housing images in old traditional architectural style with rural face, built by stone, brick and concrete in high dense vegetation were evaluated to be more energy efficient than those with modern architecture, built by large glass panel and metal cladding with light or no vegetation. Research limitations/implications: The main limitation of the paper is related to the nature of an image-based survey, which leads to ignoring some aspects of real spaces such as odour, temperature and noise. Practical implications: This research has the potential for developing a practical methodology for assessing housing-resident fit using computer-based methodology and neural networks. Social implications: This research has the potential for developing a methodology, assisting the end users in meeting their desires and motivations by helping them in assessing how a housing unit fits with their expectations and preferences. Originality/value: This research provides a reliable conceptual platform for dealing with the complexity of occupants' housing perceptions. This is achieved by establishing a collective conceptual picture of these environmental perceptions, namely, housing image, which is a platform for transferring abstract data related to human perception into measurable and quantitative scales.